2006
DOI: 10.1002/cne.21003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial exploration induces ARC, a plasticity‐related immediate‐early gene, only in calcium/calmodulin‐dependent protein kinase II‐positive principal excitatory and inhibitory neurons of the rat forebrain

Abstract: Active behavior, such as exploring a novel environment, induces the expression of the immediate-early gene Arc (activity-regulated cytoskeletal associated protein, or Arg 3.1) in many brain regions, including the hippocampus, neocortex, and striatum. Arc messenger ribonucleic acid and protein are localized in activated dendrites, and Arc protein is required for the maintenance of long-term potentiation and memory consolidation. Although previous evidence suggests that Arc is expressed in neurons, there is no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
190
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 231 publications
(228 citation statements)
references
References 70 publications
34
190
1
Order By: Relevance
“…Whereas very low levels of Arc mRNA are found in rats taken directly from their home cages ("caged control"), Arc expression is robustly, yet transiently, induced by behavioral experience. A recent study showed that Arc is induced exclusively in α calcium-calmodulin kinase II (αCaMKII) expressing principal neurons in the striatum, hippocampus, and neocortex (Vazdarjanova, Ramirez-Amaya, Insel, Plummer, Rosi, Chowdhury, Mikhael, Worley, Guzowski, & Barnes, 2006). The tight association of Arc expression with αCaMKII supports the hypothesis that Arc and αCaMKII act as "plasticity partners", which promote synaptic modifications that accompany learning in principal neurons (Vazdarjanova et al, 2006).…”
Section: Activity-regulated Arc Transcriptionmentioning
confidence: 96%
“…Whereas very low levels of Arc mRNA are found in rats taken directly from their home cages ("caged control"), Arc expression is robustly, yet transiently, induced by behavioral experience. A recent study showed that Arc is induced exclusively in α calcium-calmodulin kinase II (αCaMKII) expressing principal neurons in the striatum, hippocampus, and neocortex (Vazdarjanova, Ramirez-Amaya, Insel, Plummer, Rosi, Chowdhury, Mikhael, Worley, Guzowski, & Barnes, 2006). The tight association of Arc expression with αCaMKII supports the hypothesis that Arc and αCaMKII act as "plasticity partners", which promote synaptic modifications that accompany learning in principal neurons (Vazdarjanova et al, 2006).…”
Section: Activity-regulated Arc Transcriptionmentioning
confidence: 96%
“…Expression of these genes is regulated by excitatory synaptic transmission and, in the hippocampus, is closely related to place cell activity (Guzowski et al 1999;Guzowski 2002;Vazdarjanova et al 2006). IEGs can also be used to examine reactivation of individual neurons during two separate events.…”
Section: Identification Of Reactivated Neuronsmentioning
confidence: 99%
“…23,24 Spatial exploration also increases Arc expression, and does so specifically in glutamatergic neurons of hippocampus and neocortex. 58 Thus, the increased expression of Fos and Arc during training may reflect not just neuronal activation, but more specifically synaptic plasticity.…”
Section: Disclosure Statementmentioning
confidence: 99%